VD_FINDINFO Jug / 2016 / 378 vom 3. Mai 2016 - VD Tribunal cantonal (2016)
DÉFAUTCONTUMACE, ACTE D'ACCUSATION, COMPLÉMENT, GARANTIE DE PROCÉDURE, ÉTAT DE FAIT, INFRACTION | 325 al. 1 CPP (CH), 333 CPP (CH), 344 CPP (CH), 409 CPP (CH)